MODEL SUKSES FAKTOR WIRAUSAHA WANITA - Achmad, Nur; Saputro, Edy Purwo (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2017)
Women entrepreneurs, an important factor supporting the economy and the research, present a variety of success factors that interesting to observe. This study aims to explore these three success factors of entrepreneurship including; bank credit, training, motivational, and inspirational success through the survey stage. This analysis shows that the three success factors effect on the amount of assets, production levels, productivity, and total profit, despite the success factor has no effect on increasing the number of workers. Limitation of this study is the homogeneity of the respondents, then this probably to become a reference for the further research as well as a research gap.
Keywords: sukses faktor; wirausaha; wanita; generasi muda